2007
DOI: 10.1590/s1519-566x2007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Biologia e não-preferência para oviposição por Bemisia tabaci (Gennadius) biótipo B (Hemiptera: Aleyrodidae) em cultivares de algodoeiro

Abstract: -The purposes of this work were to evaluate some biological aspects of Bemisia tabaci (Gennadius) biotype B at egg and nymphal stages and to evaluate the non-preference for oviposition and its correlation with the number and type of trichomes on the cotton cultivars BRS Ipê, BRS 186-Precoce 3, BRS Acala, BRS Verde, BRS-200 Marrom, BRS Cedro, BRS Ita 90-2 and BRS Aroeira. The experiments were conducted in climatic chambers at 28 ± 2°C, 70% RH and photophase of 14h, and in greenhouse. Egg fertility was not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
9
0
4
Order By: Relevance
“…Satsukimidori, all larvae of this biotype died before emerging into adults on the other four kidney bean cultivars. To date, several influences of plant cultivars on the development of B. tabaci have been reported, e.g., tomato (Islam and Shunxiang, 2007); cotton (Butler et al, 1986;Torres et al, 2007); melon (Soria et al, 1999). In these reports, however, for any plant that B. tabaci larvae were able to utilize as a host, all tested cultivars of the plant species could also serve as hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Satsukimidori, all larvae of this biotype died before emerging into adults on the other four kidney bean cultivars. To date, several influences of plant cultivars on the development of B. tabaci have been reported, e.g., tomato (Islam and Shunxiang, 2007); cotton (Butler et al, 1986;Torres et al, 2007); melon (Soria et al, 1999). In these reports, however, for any plant that B. tabaci larvae were able to utilize as a host, all tested cultivars of the plant species could also serve as hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A população inicial de moscas-brancas foi proveniente do Instituto Agronômico (IAC) e previamente identificada pela Dr. a Judith K. Brown, da Universidade do Arizona, EUA, como B. tabaci biótipo B. Recentemente, confirmou-se a identidade de insetos dessa criação por meio de RAPD (Fontes et al, 2010). Para manutenção da mosca-branca, utilizaram-se plantas de couve 'Manteiga da Geórgia', em casa de vegetação (Torres et al, 2007).…”
Section: Criação De Manutenção De Bemisia Tabaci Biótipo Bunclassified
“…Essa não diferenciação de genótipos no teste sem chance de escolha após a obtenção de médias de oviposição significativamente diferentes em teste com chance de escolha com B. tabaci biótipo B também foi observada por Torres et al (2007), que avaliaram a oviposição dessa mosca-branca em genótipos de algodoeiro.…”
Section: Atratividade E Preferência Para Oviposição Nos Genótipos Selunclassified
“…In a similar study Gomez et al, (2013) had reported the lowest percentage of egg hatchability of B. tabaci on resistant chillies accessions. Previous studies with other crops such as tomato (Oriani et al, 2011;Muigai et al, 2003;Fancelli et al, 2003) cotton (Torres et al, 2007) and bean (Campos et al, 2003) had shown such differences in egg hatchability and (or) nymphal survival. Nombela et al, (2000) and Rodriguez et al, (2011) had found that oviposition of B. tabaci on tomato leaves was higher in those with higher sugar esters in the glandular exudates of type IV trichomes.…”
Section: Fig1 Non-preference For Whitefly Bemisia Tabaci Adult Settlmentioning
confidence: 87%